Analysis of LAN networks in a deep Pustu Gelebak Dalam using Cisco Packet Tracer - Nandita Nazwanilya Sahza Putri Nandita; Karnadi; M. Ihsan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Recently, the development of information and communication technology, especially computer networks, is now so rapid and has become one of the indicators of human progress. Along with these developments, users' needs for network access quality are increasing, both LAN (Local Area Network) based. The quality in question includes high data transmission speeds, stable connections, and a system that is able to support various activities without interruptions or problems that can reduce work productivity. With the existence of LAN networks, the use of information and communication technology can be an effective connecting medium. This research was carried out with the aim of helping to analyze and simulate the Local Area Network (LAN) network which is equipped with integration using the Cisco Packet Tracer application at the Gelebak Dalam Auxiliary Health Center. The presence of a LAN network will allow various processes and transactions to be carried out more efficiently, reduce potential problems, and improve the quality of services provided by institutions or organizations. This project is for that. This study will assess the condition of the LAN network at the Gelebak Dalam Auxiliary Health Center using Cisco Packet Tracer. It is anticipated that the LAN network in the health center can be optimized to be more efficient.